(untitled) - Harrell, Charles (Boston, 2004)
Simulation Using Promodel covers the art and science of simulation in general and the use of Promodel simulation software in particular. The text blends theory with practice presenting actual applications in business, services and manufacturing. This second edition reflects the most recent version of the Promodel software available, version 6.0, copyright 2003.
Keywords: Promodel,Computer simulation